Evaluation of TB Dots Surveillance System-Sindh Province 2012-13 - Naveed Masood, Jawaid Hussain Lighari, Atta Muhammad Chandio, Noor Ali Samoon, lrfan All Arbab (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
Objective: To evaluate the TB (Tuberculosis) DOTS (Directly Observed Treatment, Short Course) surveillance system in Sindh. Methods: Qualitative and quantitative assessment of system attributes was done from November 2012 to January 2013 in Sindh Province according to the CDC guidelines 2001. Available literature was reviewed. Stakeholders were identified and engaged in the evaluation process; face to face interviews were conducted with the help of structured questionnaire. The data collected was statistically analyzed and results were tabulated. Results: Case definition is simple and easy to understand. Staff is trained in data collection and dissemination to concerned authorities. System has flexibility and accepts new health related events. Data quality is good and timeliness is average; system cannot pick epidemics timely. Sensitivity was 44.6% and PPV was 45.3%.The acceptability is average with less public private collaboration and representativeness is average as system covers 2.3 districts of sindh but does not exists at most of the primary health care level. Conclusion: TB DOTS does not exist at primary care level health Facilities. There is poor response in the reporting of TB patients in the private health sectors and they do not follow TB-DOTS strategy. The routine reporting system fails in timely identification ofoutbreaks as the three months it takes for the TB data to reach from the Health Facilities to the district and provincial team does not take timely action or intervention response. No integration with other health system and less public private collaboration.